Analysis of Primary School Teacher Needs Towards Counseling and RPS Model Development Guidelines at PGMI Department of IAIN Batusangkar - Nurjani, Nurjani; Hadiarni, Hadiarni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This paper departs from an initial research survey conducted at several primary schools in Tanah Datar Regency where class teachers were less able to function as guidance and counseling teachers in addition to being class teachers. This is due to a lack of teacher knowledge related to guidance and counseling services in primary schools. Furthermore, lecturers at the university also do not teach the tools of guidance and counseling services. This research aims to identify the problems of class teachers in dealing with guidance and counseling services and developing RPS guideline and counseling in the PGMI IAIN Batusangkar department. The research was conducted using research and development methods and used the four-D model, namely definition, design, development, and dissemination. The instruments used are open numbers and validation sheets. The research findings are that the RPS BK design for the PGMI IAIN Batusangkar department was declared to have met the valid criteria with a percentage of 77.5%, and based on limited trials with 5th semester PGMI students, the percentage was 76% in the valid category.